NUCLEOTIDE SEQUENCES OF D-LOOP MITOCHONDRIAL DNA IN HUMAN MESODERM LAYER - Unwakoly, Semuel
Adult individuals originate from a single cell as the fusion of a sperm and ovum forming a zygote. Human embryo posses organelle such as mitochondria with the main function as producers of energy in cells. Mitochondria has its own genetic material, called mitochondrial DNA (mtDNA). Cell growth into many cells during embryogenesis. When the numbers of cells reached a certain level, these cells differentiated into three embryonic layers; ectoderm, mesoderm, and endoderm respectively. There are cases in which mutations in the mitochondrial genome would cause genetic. Diseases affecting all human tissues, despite the fact that some diseases only occur in certain tissues. For example, the Myoclonic Epilepsy with Ragged Red Fibers (MERRF) disease that occurs in the muscle tissue, Leber’s Hereditary Optic Neuropathy (LHON) in optic nerve tissue, and the Kaerns-Sayre Syndrome occurs in the eye tissue respectively. Recently, it is not clear whether there is a polymorphisms in mtDNA nucleotide sequence in tissues originated from each of that embryonic layer. Therefore, the purpose of this study was to determine whether there are differences in the nucleotide sequences of the human mtDNA D-loop fragment in tissues derived from the mesoderm layer.